EXAMINING DESSERT CAFÉ EXPERIENCE THROUGH THE LENS OF MALE CUSTOMERS: HOW DOES WELL-BEING PERCEPTION IMPROVE CUSTOMER CITIZENSHIP BEHAVIOUR? - Esther Sii Wei Ling; Bee-Lia Chua; Wan Melissa Wan Hassan (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
A dessert café provides an aesthetically pleasing space for meeting, relaxation, and socialising, which benefits people’s emotional and social well-being. While these cafes may have traditionally been viewed as a space for female customers, the number of male customers patronising dessert cafes has increased. Male customers’ well-being perception and citizenship behaviour are the variables of interest as they may perceive dessert café visit experience differently than female customers. The present study focuses on male dessert café customers and intends to examine the positive effect of men’s well-being perceptions in emotional and social aspects on customer citizenship behaviour (i.e., feedback, advocacy, helping, tolerance). The mediating effect of customer attitude towards dessert café between well-being perceptions and customer citizenship behaviour was investigated. A total of 115 valid responses were collected from male customers who had visited one of the selected dessert café brands. By adopting the Structural Equation Modeling method, the findings revealed a significant relationship between well-being perceptions and attitude. In addition, male customers’ attitude significantly improved customer intention to co-create discretionary value. In the mediation analysis, attitude fully mediated the relationship between well-being perceptions and customer citizenship behaviour. The results implied that when men perceived a high level of well-being during dessert café visits, they generated positive attitudes, which in turn encouraged their intention to co-create value. This study contributes to the theoretical and practical knowledge in the sector of dessert café.